The Brothers Schlemiel - Binder, Mark (Book collections on Project MUSE., 2008)
Born in Chelm, a small Jewish settlement known for being full of fools, identical twin brothers Abraham and Adam are alike in so many ways that they, themselves, are not always sure who is who, as they grow to adulthood encountering gypsies, thieves, kings, and love along the way.